A rapid and green GC-MS method for the sampling of volatile organic compounds in spices and flowers by concurrent headspace single-drop microextraction and solid-phase microextraction. Issue 12 (7th March 2023) - Gupta, Manju; Soni, Soumitra; Jain, Archana; Verma, Krishna K.
Abstract : Concurrent headspace single-drop microextraction/solid-phase microextraction has been conducted on the same sample and vial and sample preparation was completed in the time duration of a single experiment. Abstract : The equilibrium rather than the exhaustive nature of headspace single-drop microextraction (HS-SDME) and headspace solid-phase microextraction (HS-SPME) allowed the concurrent sampling of volatile organic compounds (VOCs) on the same sample in the same vial in a dual extraction configuration. This has avoided the necessity of conducting a separate set of experiments and was found to produce results in the time duration of a single sample preparation experiment. The results obtained by HS-SDME were validated against those found by the standard method of HS-SPME. Rectilinear calibration was made for certain VOCs tested as analytes over the range of 0.01–8 μg g −1, and the average values of R 2, LOD and LOQ were found to be, respectively, 0.9992, 1.9 ng g −1 and 5.7 ng g −1 in HS-SDME, and 0.9991, 3.1 ng g −1 and 9.1 ng g −1 in HS-SPME. The spiked recoveries and RSD were, respectively, 100.5% and 3.3% in HS-SDME and 98.1% and 3.6% in HS-SPME. HS-SDME is convenient to perform and produce results in a much cheaper way than HS-SPME and free from the inconveniences of memory effects. With GC-MS, this method has also been implemented as a rapid, reliable and green procedure (by GAPI and AGREE tools) for the sampling of VOCs in real samples of spices, flowers, and a beetle nut chewing sample illicitly containing tobacco.